2014
DOI: 10.1371/journal.pone.0095560
|View full text |Cite
|
Sign up to set email alerts
|

Birth of Healthy Offspring following ICSI in In Vitro-Matured Common Marmoset (Callithrix jacchus) Oocytes

Abstract: Intracytoplasmic sperm injection (ICSI), an important method used to treat male subfertility, is applied in the transgenic technology of sperm-mediated gene transfer. However, no study has described successful generation of offspring using ICSI in the common marmoset, a small non-human primate used as a model for biomedical translational research. In this study, we investigated blastocyst development and the subsequent live offspring stages of marmoset oocytes matured in vitro and fertilized by ICSI. To invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 38 publications
(40 reference statements)
1
68
0
1
Order By: Relevance
“…This short generation turnover might be shortened further if spermatids from immature animals could be used for production of the next generation. In marmosets, the protocol for ICSI has already been established (Takahashi et al, ), and we expect that it can be applied to ROSI with slight modifications. We found that late round spermatids and elongated spermatids could be collected from male marmosets at around 10–12 months of age, although this timing might show individual variations.…”
Section: Discussionmentioning
confidence: 99%
“…This short generation turnover might be shortened further if spermatids from immature animals could be used for production of the next generation. In marmosets, the protocol for ICSI has already been established (Takahashi et al, ), and we expect that it can be applied to ROSI with slight modifications. We found that late round spermatids and elongated spermatids could be collected from male marmosets at around 10–12 months of age, although this timing might show individual variations.…”
Section: Discussionmentioning
confidence: 99%
“…Embryos were collected according to established methods using recently developed devices (Takahashi et al, 2014;Thomson et al, 1994). Staging of female marmoset reproductive cycles and embryo collection have been described (Hanazawa et al, 2012).…”
Section: Marmoset Colony Maintenance and Embryo Collectionmentioning
confidence: 99%
“…The mRNA-injected embryos were cultured in ISM-1 medium (Origio) for 4 days at 37 C with 5% CO 2 , 5% O 2 , and 90% N 2 . The live embryos were then noninvasively transferred into the surrogate mothers' uteri as previously described (Marshall et al, 1997;Takahashi et al, 2014). The plasma progesterone levels of the recipients were measured once per week to monitor pregnancy.…”
Section: Microinjection and Embryo Transfermentioning
confidence: 99%